Investigation into Factors Affecting Students’ Academic Performance in Tertiary Institutions as Expressed by Undergraduates - Yusuf, Florence Adeoti; Okanlawon, Ayoade Ejiwale; Oladayo, Taiwo Rukayat (Journal of Education in Black Sea Region, 2020)
The study adopted the descriptive survey research design. Two hundred (200) undergraduates were randomly selected from four (4) randomly selected universities in Osun state. A structured questionnaire entitled Factors Affecting Students’ Academic Performance Questionnaire (FASAPQ) which had four sections was developed and validated. Frequency counts, simple and percentage and Analysis of Variance (ANOVA) were used to analyse the data collected. The findings of the study show that age had influence on students’ academic performance in tertiary institutions. The findings also revealed that the peer group had influence on students’ academic performance in tertiary institutions. The results also supported the idea that learning environment had influence on students’ academic performance in tertiary institutions. Furthermore, the difference in the students’ across institutions perception on factors affecting the academic performance of students in tertiary institutions was found insignificant (F(3,196) = 1.138, p>0.05).Based on the findings of the study, the following recommendations were made: the school counsellors should be organizing orientation programmes for new undergraduates to get them familiar with the new environment and to understand the university.